Tantangan dan Peluang Implementasi Kurikulum Merdeka di Madrasah Ibtidaiyah - Wahyudi, Imam; Zakia, Ngulam; Anam, Ruiziq Khoirul; Analistiani, Analistiani (STAI Asy-Syukriyyah, 2024)
The Kurikulum Merdeka is a policy introduced by Indonesia's Ministry of Education, Culture, Research, and Technology to create a more flexible, responsive, and relevant education system that meets the demands of globalization and the Industrial Revolution 4.0. However, its implementation in Madrasah Ibtidaiyah still faces various complex challenges. These challenges include the lack of teacher preparedness in implementing the curriculum, limited supporting learning facilities, and insufficient efforts to socialize the curriculum comprehensively. Therefore, strategic measures are needed, such as improving teacher competencies, providing adequate facilities, and intensifying socialization to ensure the optimal implementation of Kurikulum Merdeka at Madrasah Ibtidaiyah Legowetan. The researcher employed a qualitative research method with a case study approach. Data collection techniques included interviews with the Madrasah Ibtidaiyah Legowetan principal, observations, and documentation. Data analysis followed the Miles and Huberman model, comprising data reduction, data presentation, and conclusion drawing. The research findings indicate that the main challenges educators face include the need to shift teaching methods from structured approaches to more flexible, student-engaged learning. Limitations in learning media and students' readiness to adapt to the new competency-based approach also pose significant obstacles. The transformation from the 2013 Curriculum to the Kurikulum Merdeka affects how students perceive learning, which now focuses more on processes and skill development. Despite difficulties in aligning learning materials with this more flexible approach, teachers strive to create variations in teaching methods that promote student engagement and facilitate better understanding of the material